The red colobus monkeys variation in demography, behavior, and ecology of endangered species - Struhsaker, Thomas T. (Oxford : Oxford University Press, 2010)
Red colobus monkeys are very unusual in many aspects of their biology, not just among primates but also among mammals. This thorough and current review of their biology takes full account of the latest theory in optimal foraging, sexual selection, social organisation, biogeography, and conservation biology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Red colobus monkey; Red colobus monkey -- Behavior; Red colobus monkey -- Ecology